The effect of cost leadership strategies on company performance: a case of Multimedia Saatchi & Saatchi. - Chengeta, Matron (Midlands State Univeristy, 2017)
The research was carried out to find out the effect of cost leadership strategies on company performance in the advertising industry. In this research a sample of 61 respondents was used as representative of the target population. The main objectives of this research was to find out the effect of vertical integration on market share, to determine the effects of restructuring on company profitability, to evaluate whether outsourcing from cheapest supplier managed to reduce company cost. These objectives were aligned with the research problem to answer the core issues of the study. Literature put forward by various scholars, authors and researchers was compared and contrasted identifying the areas of convergence and divergence. The researcher used descriptive research to obtain insights and clarification on the research understudy and the researcher used interviews, questionnaires to obtaining raw data from the respondents on the issues of concern. The data collected from the field were presented, analyzed and interpreted from the data presentation techniques pie chart, bar graphs and tables for easy drawing of conclusions of the data. The results drawn from the research indicate that vertical integration is important to the organization as it improves efficiency, also clientele base and market share at large and that restructuring results in reduction in company cost and improving financial performance. The conclusions also indicate that outsourcing from cheapest supplier yield positive results in terms of reducing company cost and the results also shows that sourcing from cheapest supplier doesn’t necessarily mean low quality service. Therefore the researcher recommends the company to have interrelationships with stakeholders and to also to create business to business relationship not basing on profitability only. The researcher also recommends Multimedia to manage the Physical Evidence, services are intangible products, that is, they cannot be touched, seen, smelt, or felt.